Keeping up with the law: investigating lawyers' monitoring behaviour. Issue 7 (8th July 2014) - Ellis, Stephanie; Makri, Stephann; Attfield, Simon
Abstract : Purpose: – The authors wanted to provide an enriched understanding of how lawyers keep up-to-date with legal developments. Maintaining awareness of developments in an area (known as "monitoring") is an important aspect of professional's information work. This is particularly true for lawyers, who are expected to keep up-to-date with legal developments on an ongoing basis. Design/methodology/approach: – The authors conducted semi-structured interviews with a group of lawyers who authored and published current awareness content for LexisNexis – a large publishing organisation. The interviews focused on identifying the types of electronic, printed and people-based current awareness resources the lawyers used to keep up-to-date with legal developments and the reasons for their choices. Findings: – The lawyers mostly used electronic resources (particularly e-mail alerts and an electronic tool that alerted them to changes in website content), alongside interpersonal sources, such as colleagues, customers and professional contacts. Printed media, such as journals and newspapers, were used more rarely and usually to complement electronic and person-based resources. A number of factors were found to influence choice. These included situational relevance, presentation, utility and trustworthiness, the speed of content acquisition and interpretation facilitated by the resource. Originality/value: – The authors' findings enrich their understanding of lawyers' monitoring behaviour, which has so far received little direct research attention. Their design suggestions have the potential to feed into the design of new and improvement of existing digital current awareness resources. Their findings have the potential to act as "success criteria" by which these resources can be evaluated from a user-centred perspective.